Effect of FSH and eCG on alpaca (Vicugna pacos) oocyte maturation in vitro - Quispe-Gutiérrez, US (2021)
This study evaluated alpaca oocytes that developed to metaphase II (MII), using different concentrations of follicle stimulating hormone (FSH) with and without equine chorionic gonadotropin (eCG) during in vitro maturation. Oocytes were obtained from ovaries of slaughtered alpacas. Oocytes were matured in vitro for 36h in TCM-99 and supplemented in groups with different doses of FSH: 0.5, 0.25, 0μg.mL-1 and eCG: 15, 5, 0IU.mL-1. Oocytes were stained with 2% lacmoid, and examined for their nuclear status. The parameter for comparisons between groups was the percentage of oocytes in MII. There was an interaction between FSH and eCG (P<0.05). A higher percentage of oocytes in MII were obtained when using 0.5μg.mL-1 of FSH with any concentration of 15, 5 or 0IU.mL-1 of eCG [58.4±1.94% (n=78); 59.5±1.94% (n=85); 54.3±0.56% (n=81); P<0.05]. A similar percentage was also found using 0.25μg.mL-1 of FSH plus 15IU.mL-1 of eCG [52.3±1.66% (n=86); P>0.05] followed by 0.25μg.mL-1 of FSH with 5 or 0IU.mL-1 of eCG [47.3±1.94% (n=82); 45.3±1.94% (n=86); P<0.05]. The lowest maturation percentages were found using any concentration of eCG without FSH [8.2±0.73% (n=84); 8.0±0.66% (n=74); 11.4±1.23% (n=71); P<0.05]. In conclusion, the addition of eCG to the maturation medium would reduce the amount of FSH required in the in vitro maturation of alpaca oocytes.